Monocyte Chemiluminescence Traits in Gastric Cancer - O. V. Smirnova; A. A. Sinyakov; V. V. Tsukanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. A study of monocyte chemiluminescent activity at variant stages of gastric cancer.Materials and methods. The study enrolled 90 gastric cancer patients and 70 healthy donors. Spontaneous and induced chemiluminescence in monocytes was assessed for 90 min with a “BLM 3607” 36-channel chemiluminescence analyser (Russia). Opsonized zymosan-induced chemiluminescence enhancement was measured as a ratio of the areas under the induced vs. spontaneous chemiluminescence curves, the activation index. Statistical significance was estimated with the Mann—Whitney criterion (p < 0.05).Results. The maximal spontaneous monocyte chemiluminescence intensity significantly decreased in stage IV gastric cancer patients compared to the control cohort (p = 0.035). Time to maximum in spontaneous chemiluminescence increased in all gastric cancer patients vs. control (p = 0.001), and in stage IV gastric cancer vs. stage I patients (p = 0.043). The areas under a curve in spontaneous and induced monocyte chemiluminescence increased in all gastric cancer patients vs. control (p = 0.001), and in stage IV gastric cancer vs. stage I patients (p = 0.037). The activation index was higher in all gastric cancer cases compared to control (p = 0.001).Conclusion. All patients with gastric adenocarcinoma, irrespective of the stage, revealed changes in the monocyte chemiluminescence activity, i.e. a longer time to maximum in spontaneous chemiluminescence and larger area under the curve of spontaneous and induced chemiluminescence, the activation index. Maximal monocyte spontaneous chemiluminescence intensity diminished in stage IV gastric cancer compared to the control cohort. Immune activity reflected in monocyte chemiluminescence correlates with the stage of gastric adenocarcinoma.